A comparative analysis between the Rohingyas and Urdu-speaking population in Bangladesh: Repatriation or Statelessness? - Khan, Mohammad Tanzimuddin; Wara, Umme (Frontiers in Human Dynamics, 2025)
Most Rohingyas are not considered Myanmar’s citizens. The infamous 1982 Citizenship Act does not accept the Rohingyas as a qualified ethnic group and strips them of their citizenship. It confirms the state’s narrative that they are ‘foreigners, ‘illegal migrants’, or ‘Bengalis.’ The precariousness of their legal identity continues to loom large even though they took refuge in Bangladesh, crossing international boundaries. The host government has not recognized them as refugees, denying access to basic human rights in the process. It comes up with a new jargon to identify the Rohingyas as ‘Forcibly Displaced Myanmar Nationals or ‘FDMN.’ To address the needs of this vulnerable group, Bangladesh has conducted bilateral discussions with Myanmar and formalized a repatriation agreement in November 2017. Both attempts of repatriation made in 2018 and 2019 completely failed, largely due to Rohingya survivors’ unwillingness to go back to their homeland, which they believe is still not secure for them. This complication has made the Rohingya’s prospect for repatriation with their original citizenship identity bleak and uncertain. This article examines the uncertainties surrounding repatriation by comparing the legal struggle of Biharis living in Bangladesh. Approximately 300,000 Urdu-speaking Biharis have resided in Bangladesh since the partition in 1947, but were not recognized as citizens of Bangladesh due to their controversial position during the 1971 war. Unlike the Rohingyas, Biharis have mostly wanted to repatriate to Pakistan, which made possible voluntary repatriation of around 178,069 Biharis officially. Additionally, 100,000 Biharis were unofficially sent to Pakistan between 1973 and 1993. However, the problem arose for those who lived in Bangladesh without a citizenship identity and access to basic human rights for years. Abid Khan case in 2003 and the Sadaqat Khan case in 2008 officially declared all the Biharis as citizens of Bangladesh, including those born and minors in independent Bangladesh. This article attempts to explore the implications of the uncertain legal status of Rohingyas in the absence of any voluntary repatriation, comparing it with the instance of the Bihari community in Bangladesh.